Epithelial barrier formation by airway basal cells. Issue 3 (March 1997) - Erjefält, J S; Sundler, F; Persson, C G
Abstract : BACKGROUND: Epithelial shedding processes in airway inflammation and defence may produce damaged areas where basal cells are the main remaining epithelial cell type. The present study examines the capacity of basal cells to form an epithelial barrier structure after loss of columnar epithelial cells. METHODS: A technique was developed which allows selective removal of columnar epithelial cells from isolated airways. A drop of tissue adhesive glue was applied on the mucosal surface shortly after excision of guinea pig trachea and human bronchus. Gentle removal of the glue, together with attached columnar cells, left a single layer of cobbled, solitary basal cells. The tissue was kept in culture media. Morphological changes of the basal cells were monitored by immuno-histochemistry and scanning and transmission electron microscopy at several time points. RESULTS: After 20 minutes the basal cells had undergone extensive flattening and established contact with each other. The basement membrane thus became covered by a poorly differentiated epithelium in both guinea pig and human airways. Abundant interdigitating cytoplasmic protrusions were observed at cell borders. CONCLUSIONS: Basal cells promptly flatten out to cover the basement membrane at loss of neighbouring columnar cells. These data may explain why the epithelial barrier function may be uncompromised in desquamative airway diseases. Furthermore, they suggest the possibility that sacrificial release of columnar epithelial cells and prompt creation of a barrier structure constitute important roles of basal cells in airway defence against severe insults.